Antibiotic exposure perturbs the bacterial community in the small brown planthopper Laodelphax striatellus. (29th April 2019) - Zhang, Xu; Li, Tong‐Pu; Zhou, Chun‐Ying; Zhao, Dian‐Shu; Zhu, Yu‐Xi; Bing, Xiao‐Li; Huang, Hai‐Jian; Hong, Xiao‐Yue
Abstract: Bacteria symbionts in herbivores play an important role in host biology and ecology, and are affected by environmental factors such as temperature, diet, habitat, antibiotics and so on. However, the effects of antibiotics on the microbiome of the small brown planthopper Laodelphax striatellus (SBPH) remain unclear. Here, we studied the effects of tetracycline on the diversity and composition of bacterial colonies in different tissues of SBPH using high throughput sequencing of 16S ribosomal RNA amplicons. Our results show that Proteobacteria, Firmicutes, Bacteroidetes, Actinobacteria were most abundant in SBPH, and the genera Asaia and Wolbachia were most abundant in all body parts of SBPH. Antibiotic treatment had persistent effects on the composition of the SBPH microbiome. Tetracycline depleted the population of Firmicutes, Bacteroidetes, Tenericutes and Fusobacteria, and nearly 100% eliminated Wolbachia, Bacteroides and Abiotrophia in SBPH. Together, these results suggest that antibiotic exposure affects the bacteria symbionts of different body parts in SBPH and will facilitate future studies of the bacterial symbionts of arthropod hosts.